Cryoballoon ablation for paroxysmal atrial fibrillation: mid‐term outcome evaluated by ECG monitoring with an implantable loop recorder. (18th March 2021) - Maj, Riccardo; De Ceglia, Sergio; Piazzi, Elena; Pozzi, Mattia; Montemerlo, Elisabetta; Casiraghi, Mirko; Fienga, Marianna; Gressoni, Sara; Rovaris, Giovanni
Abstract: Background: The success rate after cryoballoon ablation (CB‐A) performed for paroxysmal atrial fibrillation (PAF) might be overestimated by traditional noninvasive monitoring techniques. The purpose of this study was to evaluate the mid‐term outcome of CB‐A in patients with PAF implanted with an implantable loop recorder (ILR) after the procedure. Methods: Between January 2017 and March 2019, all patients who underwent CB‐A for PAF and who were subsequently implanted with an ILR were retrospectively included. All devices were equipped with remote monitoring. All ILR‐documented atrial tachycardia (AT) or AF episodes ≥ 6 min were considered as recurrence; both true and false episodes were collected. A 3‐month post‐procedural blanking period (BP) was applied. Results: A total of 102 patients (77 men, mean age 60.6 ± 9.6 years) who underwent pulmonary vein isolation (PVI) by CB‐A were included; mean time from first diagnosis of AF to PVI was 51.5 ± 46.9 months. Mean follow‐up was 29.3 ± 8.1 months; at 12‐month follow‐up, the success rate was 65.7%, while at 2‐year follow‐up, freedom from AT/AF recurrences was achieved in 59.3% of the patients. In the follow‐up, a total of 4987 ECG strips were analyzed; true‐positive episodes were confirmed in 2026 cases (40.6%), whereas 2961 episodes (59.4%) were considered false‐positive. Conclusion: In patients with PAF implanted with an ILR, CB‐A results in freedom from any AT/AF recurrence in 65.7% of patients at 12‐month follow‐up and in 59.3% of patients when evaluated at 2‐year. Careful adjudication of all ILR‐documented AF episodes is required to avoid misdiagnosis.